Pengaruh Penerapan Universal Precaution (Hand Higiene dan APD) dalam Mencegah Insiden Hepatitis C pada Pasien Hemodialisa di RSU PKU Muhammadiyah Yogyakarta - Mashuri Mashuri (Universitas Muhammadiyah Yogyakarta, 2015)
Background: Hepatitis C is caused by hepatitis C virus (HCV); a small RNA virus which is wrapped by fat, its diameter is around 30 to 60 nm. An acute HCV infection is generally asymptomatic or minimally symptomatic. There are fi ve basic guidelines according to the KDIGO (Kidney Disease Improving Global Outcomes) for the prevention, diagnosis, evaluation, and treatment of hepatitis C in chronic kidney disease (Chronic Kidney Disease).Methods: The design of this research was descriptive analytic design with cross sectional approach. The population was 18 haemodyalisis patients with HCV rapid test negative on assessment in March 2012 and the sampling technique was total sampling. This study consisted of 5 independent variable application of universal precautions (hand hygiene, the use of handscoen, the use of masks, the use goggle and the use of dress/apron), and one dependent variable: the incident of hepatitis C. The instruments were: observation sheets (checklist) for universal precautions implementation and the resultsof EIA (=ELISA/ Enzyme Linked Immuno Assay) laboratory tests for hepatitis C incidents. Data analysis was uniariat and multivariate analysis (nominal regression test).Results: hand hygiene signifi cantly aff ected the incidence of hepatitis C with probability value 0.012, as well as the use of handscoen signifi cantly aff ected the incidence of hepatitis C with probability value 0.002, while the use of masks had no signifi cant eff ect on the incidence of hepatitis C due to probability value 1.000, while the statistical value of the use of goggle glasses and dress/apron weren’t found because none of the nurses wore goggle glasses and apron when caring hemodyalisis patient for both with isolation (positive hepatitis B) and without isolation (hepatitis C positive/negative). In general, the application of universal precautions had signifi cant eff ect in preventing the incident of hepatitis C with a probability value of 0.000.Conclusion: There was signifi cant eff ect of implementation of universal precautions (hand hygiene and PPE) in preventing the incident of hepatitis, especially for hand hygiene (hand wash) and the use of gloves (handscoen).Keywords: universal precautions, the incidence of hepatitis C